Pendekatan Pembelajaran Tematik Integratif dan Pengaruhnya terhadap Konsep Sekolah Ramah Anak di Madrasah Ibtidaiyah - Susanti, Yuliana (MASALIQ, 2023)
This study aims to determine the extent to which the application of integrative thematic learning influences the concept of child-friendly schools in Madrasah Ibtidaiyah. This type of research is literature study research, namely conducting research by searching for literature that supports the research and also collecting data that is relevant to the topic under study. The results of the study show that the integrative thematic learning approach is in accordance with the learning principles of the child-friendly school concept, namely student-centered learning with the principle of learning while playing and having fun. In addition, this thematic learning approach provides learning experiences and the process of developing the diversity of characters and potential of students without any discriminatory treatment both inside and outside the classroom. Learning outcomes are in accordance with the interests and needs of students because the assessment is process-based and emphasizes authentic assessment. The application of an integrative thematic learning approach has a significant effect on the concept of child-friendly schools in Madrasah Ibtidaiyah.